Strategi Pencegahan Korupsi dalam Penegakan Hukum Lalu Lintas: Mewujudkan Transparansi dan Akuntabilitas - Firyal Nuha Desiana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Corruption has become a serious problem that hinders the development of various sectors, including traffic law enforcement. Corrupt practices in this sector not only harm the state, but also threaten the safety and comfort of society. Achieving transparency and accountability in traffic law enforcement is very important. This strategy must not only involve changes to regulations, but also requires increasing the capacity and integrity of law enforcement officials, as well as active involvement of the community in supervision. Preventing corruption in traffic law enforcement requires implementing these solutions in an integrated manner, so that it is hoped that traffic law enforcement in Indonesia can become more transparent, accountable and free from corruption. These efforts will not only improve the quality of law enforcement, but also increase public trust in law enforcement institutions, which will ultimately contribute to public safety and welfare.